Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Answer:
Consistent dependent
3x - 3y = 6 and -x + y = -2
Step-by-step explanation:
Inconsistent: parallel lines, no solutions
Consistent dependent: same line, infinite solutions
Consistent independent: intersects at one point, one solution
Therefore, the pair of lines are Consistent dependent
From inspection of the diagram:
The lines will have equivalent equations.
Therefore, the solution is 3x - 3y = 6 and -x + y = -2
Because:
3x - 3y = 6 ⇒ y = x - 2
-x + y = -2 ⇒ y = x - 2
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.